Analysis of Indonesia's Coffee Export Trade Patterns to ASEAN Countries in 2011-2024 - Fauzan, Ahmad; Setyowati, Eni (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: Coffee is a commodity that is very popular with the people at home and abroad. In Indonesia, coffee has economic value and is an attraction for an agrarian country. Where in the agricultural sector, especially in coffee commodities, Indonesia has many characteristics that other coffee does not have. This study aims to provide an overview of how coffee exports in Indonesia can affect state revenue, distance between countries and also exchange rates. Methodology: Using the Poisson Pseudo Maximum Likelihood (PPML) regression model, the Gravity model. Using panel data from all countries that joined ASEAN in 2011-2024. Based on the results of this study, it is shown that the GDP variables of the country of origin and the distance between countries have a significant negative influence on the value of Indonesian coffee exports.Results: Meanwhile, the variables of the GDP of the destination country and the exchange rate have a significant positive effect on the value of Indonesia's coffee exports.Applications/Originality/Value: The Gravity model using PPML regression provides much more accurate estimates in the context of bilateral trade data that are often zero, so that they can be used as a basis for other commodity trade policy analysis. Integrating exchange rate and distance factors simultaneously to see how these variables relate to the value of Indonesian coffee exports, enriching the economic literature of agricultural commodity trade. It offers an empirical basis for policymakers to develop more appropriate strategies to improve Indonesia's coffee export performance through exchange rate strengthening, logistics efficiency, and mapping market opportunities in ASEAN.